Platelet Adhesion from Nonanticoagulated Rat Arterial Blood* - Bern, Murray M.; Tullis, James L. (Thrombosis and Haemostasis, 1974)
Platelet adhesion to glass bead is measured using nonanticoagulated arterial blood from adult male rats. Parameters studied include: 1) surface area of glass exposed to platelets, 2) time of contact and rate of platelet flow over the beads, 3) differing blood-gas interface, 4) adhesion to siliconized polyvinyl surfaces, and 5) heparinization of donors. Parameters kept constant include: 1) diameter of glass beads, 2) diameter of glass bead chamber, and 3) body temperature of the donor animals. No air was mixed with the blood. Concentration of hemoglobin released into the plasma supernatant was measured.Platelet adhesion from each aliquot of each sample increases as glass surface area increases, and the time of contact between the platelets and surface increases. Adhesion did not change when nitrogen was substituted for room air at blood-gas interface. Heparinization of donor animal did not alter adhesion. Platelets adhere to siliconized polyvinyl at greater rate than to nonsiliconized polyvinyl. Hemoglobin concentration in the plasma supernate did not correlate directly with percent of platelet adhesion. These results are similar to those reported for native and anti-coagulated venous and anticoagulated arterial blood.This technique does not require in vitro handling of platelets. It can be applied to other animals and to humans.